Interesting presentation of Kounis syndrome secondary to amoxicillin/clavulanate use: Coronary vasospasm and simultaneous appropriate implantable defibrillator shock - Uğur Canpolat; Duygu Koçyiğit; Kudret Aytemir (KARE Publishing, 2017)
Kounis syndrome (KS) is defined as concurrent acute coronary syndrome and allergic or hypersensitivity reactions. Despite being increasingly reported, it is still an underdiagnosed entity. Several medications are already known to result in KS. Amoxicillin/clavulanic acid is a frequently used antibiotic, and its use has been linked with KS. The aim of the present report was to draw attention to rare clinical manifestation of KS following peroral amoxicillin/clavulanate use.